Carbon Anode Materials for Rechargeable Alkali Metal Ion Batteries and in-situ Characterization Techniques - Ding, Ruida; Huang, Yalan; Li, Guangxing; Liao, Qin; Wei, Tao; Liu, Yu; Huang, Yanjie; He, Hao (Frontiers in Chemistry, 2020)
Lithium-ion batteries (LIBs), as one of energy supply and storage equipments, have been widely applied in consumer electronics, electric vehicles and energy storage systems. However, the urgent demand for high energy density batteries and the shortage of lithium resources drive scientists to develop high-performance materials and find alternatives. Low-volume expansion carbon material is the ideal choice of anode material. However, the low specific capacity has gradually become the shortcoming for the development of LIBs and thus devoloping new carbon material with high specific capacity is urgently needed. In addition, developing alternatives of LIBs, such as sodium ion batteries and potassium-ion batteries, also puts forward demands for new type carbon materials. As all known, the design of high-performance electrodes requires deep understanding on the working mechanism and the structural evolution of active materials. On this issue, ex-situ techniques have been widely applied to investigate the electrode materials under special working condition and provides a lot of information. Unfortunately, these observed phenomena are difficult to reflect reaction under real working conditions and some important short-lived intermediate products cannot be captured, leading to an incomplete understanding of the working mechanism. In-situ techniques can observe the changes of active materials in operando during the charge/discharge processes, providing the concrete process of solid electrolyte formation, ions intercalation mechanism, structural evolutions, etc. Herein, this review aims to provide an overview on the characters of carbon materials in alkali ion batteries and the role of in-situ techniques in devoloping carbon materials.